Molybdenum oxide-molybdenum disulfide poly-tannic acid electrode material and preparation method and application thereof

By preparing molybdenum oxide-molybdenum disulfide@polytannic acid electrode materials, the self-discharge and inflammation problems of supercapacitors in IME were solved, realizing high-performance, biodegradable supercapacitors suitable for flexible electronic devices and biomedical implants.

CN121075823AActive Publication Date: 2025-12-05ANHUI UNIVERSITY OF TRADITIONAL CHINESE MEDICINE
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511190849.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-25
Publication Date
2025-12-05
Estimated Expiration
2045-08-25

AI Technical Summary

Technical Problem

Self-discharge of supercapacitors in implantable medical electronic devices (IMEs) can lead to voltage drops and current leakage, affecting normal operation. In addition, the components may trigger inflammatory responses in the body, and traditional supercapacitors require a second surgery to remove them, increasing the burden on patients.

Method used

A biodegradable supercapacitor electrode was prepared by using molybdenum oxide-molybdenum disulfide@polytannic acid electrode material, growing molybdenum oxide nanosheets by anodic oxidation, and combining hydrothermal reaction and ultraviolet light deposition of polytannic acid coating. Biodegradable electrolyte and encapsulation materials were also used.

Benefits of technology

It effectively suppresses self-discharge behavior, improves electrode conductivity and electrochemical activity, extends working time, reduces charge loss, and the material is biodegradable to avoid environmental pollution, reduces inflammatory response, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121075823A_ABST
    Figure CN121075823A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of supercapacitors, and particularly relates to a molybdenum oxide-molybdenum disulfide poly-tannic acid electrode material and a preparation method and application thereof. Molybdenum foil is used as a current collector and an electrode, an electrochemical oxidation method and a hydrothermal method are adopted to prepare a molybdenum oxide-molybdenum disulfide electrode, a poly-tannic acid coating is deposited on the surface of the molybdenum oxide-molybdenum disulfide electrode, and the degradable molybdenum oxide-molybdenum disulfide poly-tannic acid electrode is prepared. A sandwich structure is formed by the composite material and a degradable gel electrolyte, and is packaged by a degradable packaging material, so that the degradable supercapacitor with a self-discharge suppression function is constructed. The self-discharge behavior of the super capacitor is inhibited by depositing the poly-tannic acid coating on the surface of the electrode of the super capacitor, and the poly-tannic acid coating can prevent parasitic Faraday reaction of foreign ions on the surface of the electrode and prevent charge transfer, so that the self-discharge behavior of the capacitor is inhibited; and meanwhile, the electrode, the electrolyte and the packaging material can be degraded in simulated body fluid, so that the application of the electrode, the electrolyte and the packaging material in implantable medical electronic devices is expected to be developed.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of supercapacitors, and particularly relates to a molybdenum oxide-molybdenum disulfide@polytannic acid electrode material and a preparation method and application thereof. BACKGROUND

[0002] With the development of modern medical technology, implantable medical electronic devices (IME) have become an important part of the healthcare system. Because it can sense specific physicochemical parameters in the human body and stimulate target tissues or organs or deliver drugs, it can achieve accurate diagnosis and treatment of diseases. Generally, IME is mainly composed of programming circuit, actuator and energy supply device modules, among which the energy supply device is the core component to drive the electronic device to run stably in the body.

[0003] Supercapacitors (SCs) are expected to solve the energy supply needs of IME due to their high power density, long cycle life and fast charging and discharging rates. However, the Gibbs free energy of SCs in the charging state is higher than that in the discharging state, which leads to a serious self-discharge phenomenon, resulting in voltage drop, current leakage and capacity loss, affecting its normal operation. In addition, during the implantation into the body, the components of the capacitor (including electrodes, electrolyte, packaging layer) may cause inflammation in the body, and it usually needs to be removed by secondary surgery after completing the biomedical task, which will bring additional burden to the patient's body and economy. SUMMARY

[0004] To solve the above problems, in a first aspect, the application provides a preparation method of a molybdenum oxide-molybdenum disulfide@polytannic acid electrode material, characterized in that it comprises the following steps: growing molybdenum oxide nanosheets on the surface of the cleaned molybdenum foil by an anodic oxidation method; adding thiourea to the reaction container containing the molybdenum oxide nanosheets to perform a hydrothermal reaction to prepare a molybdenum oxide-molybdenum disulfide electrode material; placing the molybdenum oxide-molybdenum disulfide electrode material in a tannic acid buffer solution, irradiating it with ultraviolet light, depositing a polytannic acid coating on the surface of the electrode material, and obtaining a molybdenum oxide-molybdenum disulfide@polytannic acid electrode material.

[0005] Further, the method further comprises ultrasonic cleaning the molybdenum foil with hydrochloric acid, acetone, anhydrous ethanol and purified water in sequence. The anodic oxidation method uses a three-electrode system, the voltage window is 0~0.8V, the scanning rate is 0.08~0.1Vs -1 , and the oxidation time is 4~10 minutes.

[0006] Further, the specific conditions of the hydrothermal reaction are as follows: hydrothermal reaction at 160~200℃ for 10~14 hours. The concentration of the thiourea solution is 0.5-1.0 M; specifically, the thiourea concentration can be 0.5 M, 0.8 M, 1.0 M, and the preferred thiourea concentration is 0.8 M.

[0007] Further, the buffer solution is a Tris-HCl buffer solution, and the concentration is 5-20 mM; specifically, the Tris-HCl buffer solution concentration is 5, 10, 20 mM, and the preferred Tris concentration is 10 mM; The concentration of the tannic acid in the buffer solution is 5-20 mg / mL; specifically, the tannic acid concentration is 5, 10, 20 mg / mL, and the preferred tannic acid concentration is 10 mg / mL; The wavelength of the ultraviolet light is 254-365 nm, and the irradiation time is 0.5-5 hours; specifically, the wavelength of the ultraviolet light is 254, 280, 310, 365 nm, and the irradiation time is 0.5, 1, 2, 3, 5 hours. The preferred wavelength is 254 nm, and the irradiation time is 2 hours.

[0008] In a second aspect, the present application provides a degradable molybdenum oxide-molybdenum disulfide@polytannic acid electrode material prepared by the preparation method.

[0009] In a third aspect, the present application provides a method for inhibiting the self-discharge behavior of a supercapacitor, which uses the molybdenum oxide-molybdenum disulfide@polytannic acid electrode material as the electrode of the supercapacitor.

[0010] In a fourth aspect, the present application provides a molybdenum oxide-molybdenum disulfide@polytannic acid supercapacitor, which comprises a first electrode layer, a second electrode layer, and an electrolyte layer arranged between and in contact with the first electrode layer and the second electrode layer. The first electrode layer and / or the second electrode layer is the molybdenum oxide-molybdenum disulfide@polytannic acid electrode material; The electrolyte layer is a polyvinyl alcohol / sodium chloride gel electrolyte.

[0011] In a fifth aspect, the present application provides a preparation method of a molybdenum oxide-molybdenum disulfide@polytannic acid supercapacitor, which comprises the following steps: Dissolve polyvinyl alcohol in a sodium chloride solution at a concentration of 0.1-0.3 g / mL, stir until the solution is transparent, and then stand to obtain a polyvinyl alcohol / sodium chloride gel electrolyte; Coat the surfaces of the first electrode layer and the second electrode layer of claim 7 with the polyvinyl alcohol / sodium chloride gel electrolyte, paste the coated first electrode layer and the second electrode layer to form a primary supercapacitor; The polylactic acid-glycolic acid copolymer and chloroform are mixed in a ratio of 0.01-0.03:1 g / mL, ultrasonic dissolution is carried out, and then the polylactic acid-glycolic acid copolymer is coated on the surface of the super capacitor; and the super capacitor is placed under ventilation for 10-14 hours. The super capacitor after ventilation is immersed in a liquid obtained by mixing and melting beeswax and candelilla wax, and after being taken out, the molybdenum oxide-molybdenum disulfide@polytannic acid super capacitor after encapsulation is obtained after natural drying at room temperature.

[0012] Further, in the preparation process of the polyvinyl alcohol / sodium chloride gel electrolyte: The concentration of the sodium chloride solution is 0.5-2 M; The dissolution conditions of the polyvinyl alcohol in the sodium chloride solution are as follows: stirring at room temperature for 20-40 minutes, and then stirring at 80-100 DEG C for 2-4 hours after heating; The standing condition is standing at 2-6 DEG C for 12-24 hours.

[0013] Further, the use amount ratio of the polylactic acid-glycolic acid copolymer and chloroform is 0.01-0.03:1 g / mL; The mass ratio of the beeswax and candelilla wax is 2-4:1; The heating temperature of the beeswax and candelilla wax is 70-90 DEG C.

[0014] The beneficial effects of the application are as follows: By depositing the polytannic acid coating on the surface of the super capacitor electrode, the self-discharge behavior of the super capacitor can be effectively inhibited. The polytannic acid coating can reduce the side reaction between the electrode and the electrolyte, reduce the loss rate of electric charge, and make the super capacitor maintain the electric quantity for a longer time during storage, thereby significantly improving the energy saving capacity and prolonging the effective working time.

[0015] The molybdenum oxide-molybdenum disulfide@polytannic acid electrode material adopted in the application has an optimized preparation process, which not only ensures the good conductivity and electrochemical activity of the electrode material, but also further improves the cycle stability and specific capacitance of the electrode through the modification of the polytannic acid coating, so that the performance of the super capacitor slowly decays during the charging and discharging cycle process, and the super capacitor can work stably for a long time.

[0016] The prepared supercapacitor comprises a biodegradable material for each component, including an electrode layer, an electrolyte layer and a packaging material. The electrode layer material, molybdenum disulfide@polytannic acid, has a biodegradable property, the biodegradable electrolyte layer selects PVA gel, and the packaging material uses biodegradable materials such as polylactic acid-glycolic acid copolymer (PLGA), beeswax and candelilla wax, thereby avoiding the pollution problem caused by traditional electronic devices after being discarded, meeting the development trend of green environmental protection, reducing the generation of electronic waste, and being conducive to the protection of the ecological environment. The biodegradable material can be gradually degraded into low molecular weight compounds or monomers through hydrolysis or enzymatic degradation, and finally be absorbed or excreted by the body through metabolism. On the one hand, the biodegradable material can avoid the side effects caused by secondary surgery removal, and on the other hand, it can also reduce the inflammatory response of the body. The biodegradable material is applied to the capacitor and inhibits the self-discharge behavior, which has important significance in promoting the further clinical application of IME.

[0017] In terms of preparation and application, the related preparation method steps are clear and operable, the raw materials involved are easy to obtain, and no complex or high-pollution process is used in the preparation process, which is suitable for large-scale production. At the same time, the manufacturing method of the supercapacitor is simple, the assembly and packaging process is easy to control, and the consistency and stability of the product can be guaranteed. The good performance and biodegradable property make it have broad application prospects in flexible electronic devices, biomedical implant devices, environmental monitoring equipment and other fields, meeting the needs of different scenes for high-performance and environmentally friendly energy storage devices.

[0018] Other features and advantages of the present application will be set forth in the following description, and in part will become apparent to those skilled in the art from the description, or can be learned by practice of the application. The objects and other advantages of the present application can be achieved and obtained by the structures indicated in the specification, claims and drawings. BRIEF DESCRIPTION OF DRAWINGS

[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the following will briefly introduce the drawings needed to be used in the embodiment or prior art description. Obviously, the drawings in the following description are some embodiments of the present application, and those skilled in the art can also obtain other drawings according to these drawings without creative labor.

[0020] Figure 1The cyclic voltammetry (CV) curve, galvanostatic charge-discharge (GCD) curve, specific capacitance line contrast chart, and electrochemical impedance (EIS) spectrum of the molybdenum oxide-molybdenum disulfide@polytannic acid electrode prepared in different tannic acid concentrations (5, 10, 20 mg / mL) of the embodiment 1, 3, 5 of the application are shown in FIG. 1. Wherein a) is the CV contrast chart of the molybdenum oxide-molybdenum disulfide@polytannic acid electrode prepared in different tannic acid concentrations at 100 mV s -1 , b) is the GCD contrast chart of the molybdenum oxide-molybdenum disulfide@polytannic acid electrode prepared in different tannic acid concentrations at 0.5 mA cm -2 , c) is the specific capacitance contrast chart of the molybdenum oxide-molybdenum disulfide@polytannic acid electrode prepared in different tannic acid concentrations, d) is the EIS contrast chart of the molybdenum oxide-molybdenum disulfide@polytannic acid electrode, e) and f) are the CV curve and GCD curve of the molybdenum oxide-molybdenum disulfide@polytannic acid electrode prepared in the preferred tannic acid concentration of 10 mg / mL at 5, 10, 20, 30, 40, 50, 100 mV s -1 , and 0.5, 1, 2, 4, 6, 8 mA cm -2 , respectively.

[0021] Figure 2 The cyclic voltammetry (CV) curve, galvanostatic charge-discharge (GCD) curve, specific capacitance line contrast chart, and self-discharge curve of the molybdenum oxide-molybdenum disulfide@polytannic acid capacitor (tannic acid concentration of 5, 10, 20 mg / mL) prepared in the embodiment 2, 4, 6 of the application are shown in FIG. 2. Wherein a) is the CV contrast chart of the molybdenum oxide-molybdenum disulfide@polytannic acid capacitor prepared in different tannic acid concentrations at 100 mVs -1 , b) is the GCD contrast chart of the molybdenum oxide-molybdenum disulfide@polytannic acid capacitor prepared in different tannic acid concentrations at 0.5 mA cm -2 , c) is the specific capacitance contrast chart of the molybdenum oxide-molybdenum disulfide@polytannic acid capacitor prepared in different tannic acid concentrations, d) is the self-discharge contrast chart of the molybdenum oxide-molybdenum disulfide@polytannic acid capacitor, e) and f) are the CV curve and GCD curve of the molybdenum oxide-molybdenum disulfide@polytannic acid capacitor prepared in the preferred tannic acid concentration of 10 mg / mL at 5, 10, 20, 30, 40, 50, 60, 80, 100 mVs -1 , and 0.5, 1, 2, 4, 6, 8 mA cm -2 , respectively.

[0022] Figure 3The cyclic voltammetry (CV) curve, galvanostatic charge-discharge (GCD) curve, specific capacitance line contrast chart and electrochemical impedance (EIS) spectrum of the molybdenum oxide-molybdenum disulfide@polytannic acid electrode prepared by different Tris concentrations (5, 10, 20 mM) of the present application embodiment 3, 7, 9 are shown in the figure. Wherein a) is the CV contrast chart at 100 mV s -1 scanning rate, b) is the GCD contrast chart at 0.5 mA cm -2 current density, c) is the specific capacitance result contrast chart calculated according to the discharge time, d) is the EIS contrast chart, e) and f) are the CV curve and GCD curve of the molybdenum oxide-molybdenum disulfide@polytannic acid electrode prepared by the preferred Tris concentration of 10 mM at 5, 10, 20, 30, 40, 50, 100 mV s -1 scanning rate and at 0.5, 1, 2, 4, 6, 8 mA cm -2 current density.

[0023] Figure 4 The cyclic voltammetry (CV) curve, galvanostatic charge-discharge (GCD) curve, specific capacitance line contrast chart and self-discharge curve of the molybdenum oxide-molybdenum disulfide@polytannic acid capacitor prepared by different Tris concentrations (5, 10, 20 mM) of the present application embodiment 4, 8, 10 are shown in the figure. Wherein a) is the CV curve contrast chart at 100 mV s -1 scanning rate, b) is the GCD curve contrast chart at 0.5 mA cm -2 current density, c) is the specific capacitance line contrast chart calculated according to the discharge time, d) is the self-discharge curve contrast chart of the capacitor, e) and f) are the CV curve and GCD curve of the molybdenum oxide-molybdenum disulfide@polytannic acid capacitor prepared by the preferred Tris concentration of 10 mM at 5, 10, 20, 30, 40, 50, 60, 80, 100 mV s -1 scanning rate and at 0.5, 1, 2, 4, 6, 8 mA cm -2 current density.

[0024] Figure 5 The cyclic voltammetry (CV) curve, galvanostatic charge-discharge (GCD) curve, specific capacitance line contrast chart and electrochemical impedance (EIS) spectrum of the molybdenum oxide-molybdenum disulfide@polytannic acid electrode prepared by different deposition times (0.5, 2, 5 hours) of the present application embodiment 3, 11, 13 are shown in the figure. Wherein a) is the CV curve contrast chart at 100 mV s -1 scanning rate, b) is the GCD curve contrast chart at 0.5 mA cm -2GCD curves at different current densities, c) is the specific capacitance results comparison chart calculated according to the discharge time, d) is the EIS comparison chart, e) and f) are the molybdenum oxide-molybdenum disulfide@polytannin capacitor prepared by the preferred deposition time of 2 hours respectively at 5, 10, 20, 30, 40, 50, 100 mV s -1 CV curves at different scan rates and at 0.5, 1, 2, 4, 6, 8 mA cm -2 GCD curves at different current densities.

[0025] Figure 6 CV curves of molybdenum oxide-molybdenum disulfide@polytannin capacitors prepared by different deposition times of examples 4, 12 and 14 of the present application, GCD curves, specific capacitance comparison chart, self-discharge curves. Wherein a) is the CV curve of the molybdenum oxide electrode prepared by different oxidation times at 100 mV s -1 CV curve comparison chart at different scan rates, b) is the CV curve of the molybdenum oxide electrode prepared by different oxidation times at 0.5 mA cm -2 GCD curve comparison chart at different current densities, c) is the specific capacitance comparison chart calculated according to the discharge time, d) is the self-discharge curve comparison chart of the capacitor, e) and f) are the molybdenum oxide-molybdenum disulfide@polytannin capacitor prepared by the preferred deposition time of 2 hours respectively at 5, 10, 20, 30, 40, 50, 60, 80, 100 mV s -1 CV curves at different scan rates and at 0.5, 1, 2, 4, 6, 8 mA cm -2 GCD curves at different current densities.

[0026] Figure 7 CV curves of molybdenum oxide electrodes prepared by different oxidation times (4, 6, 10 minutes) of the present application comparative examples 1-3 and molybdenum oxide@polytannin electrode prepared by comparative example 5, GCD curves, specific capacitance comparison chart, EIS spectrum. Wherein a) is the CV curve of the molybdenum oxide electrode prepared by different oxidation times at 100 mV s -1 CV curve comparison chart at different scan rates, b) is the CV curve of the molybdenum oxide electrode prepared by different oxidation times at 0.5 mA cm -2 GCD curve comparison chart at different current densities, c) is the specific capacitance comparison chart calculated according to the discharge time of the molybdenum oxide electrode prepared by different oxidation times, d) is the EIS comparison chart of the molybdenum oxide electrode prepared by different oxidation times, e) is the CV curve comparison chart of the molybdenum oxide electrode prepared by the preferred oxidation time of 6 minutes and the electrode of comparative example 3 in which tannin is deposited on the preferred molybdenum oxide at 100 mV s -1 CV curve comparison chart at different scan rates, f) is the CV curve of the molybdenum oxide electrode prepared by different oxidation times at 0.5 mA cm -2 GCD curve comparison chart at different current densities, g) is the specific capacitance comparison chart calculated according to the discharge time, h) is the EIS comparison chart.

[0027] Figure 8 Cyclic voltammograms (CV), galvanostatic charge-discharge (GCD) curves, specific capacitance comparison plots, self-discharge curves of the molybdenum oxide capacitor prepared for the present application comparative example 4 and the molybdenum oxide@polytannin capacitor prepared for comparative example 6. Wherein a) is the CV curve comparison plot at 100 mV s -1 CV curve comparison plot at 100 mV s -2 GCD curve comparison plot at 0.5 mA cm -1 CV curve comparison plot at 100 mV s and GCD curve at 0.5, 1, 2, 4, 6, 8 mA cm -2 GCD curve at 0.5 mA cm.

[0028] Figure 9 Cyclic voltammograms (CV), galvanostatic charge-discharge (GCD) curves, specific capacitance comparison plots, electrochemical impedance (EIS) spectra of the molybdenum oxide-molybdenum disulfide electrodes prepared for the present application comparative examples 7-9 with different thiourea concentrations (0.5, 0.8, 1.0 M). Wherein a) is the CV curve comparison plot at 100 mV s -1 CV curve comparison plot at 100 mV s -2 GCD curve comparison plot at 0.5 mA cm -1 CV curve comparison plot at 100 mV s and GCD curve at 0.5, 1, 2, 4, 6, 8 mA cm -2 GCD curve at 0.5 mA cm.

[0029] Figure 10 Cyclic voltammograms (CV), galvanostatic charge-discharge (GCD) curves, specific capacitance comparison plots, self-discharge curves of the molybdenum oxide-molybdenum disulfide capacitor prepared for comparative example 10 and the molybdenum oxide-molybdenum disulfide@polytannin capacitor prepared for example 4. Wherein a) is the CV curve comparison plot at 100 mV s -1 CV curve comparison plot at 100 mV s -2GCD plots at different current densities, c) is the specific capacitance results calculated from discharge time, d) is the self-discharge plots of the capacitor, e) and f) are the preferred molybdenum oxide-molybdenum disulfide@polytannic acid capacitor respectively at 5, 10, 20, 30, 40, 50, 60, 80, 100 mV s -1 CV plots at different scan rates and at 0.5, 1, 2, 4, 6, 8 mA cm -2 GCD plots at different current densities.

[0030] Figure 11A The molybdenum oxide-molybdenum disulfide@polytannic acid electrode prepared in Example 4 was tested at 3 mA cm -2 Cycle plots at different current densities, the attached figure is the GCD plots comparison of the first three and the last three cycles.

[0031] Figure 11B The molybdenum oxide-molybdenum disulfide@polytannic acid capacitor prepared in Example 4 was tested at 2 mA cm -2 Cycle plots at different current densities, the attached figure is the LED light, timer chart after the capacitor is connected in series.

[0032] Figure 12A Optical picture of the molybdenum oxide-molybdenum disulfide@polytannic acid electrode sheet prepared in Example 4 immersed in 0.1 M phosphate buffer (PBS) solution at 37°C for 15 weeks; Figure 12B Mass change plot of the molybdenum oxide-molybdenum disulfide@polytannic acid electrode sheet prepared in Example 4 immersed in 0.1 M phosphate buffer (PBS) solution at 37°C for 15 weeks; Figure 12C Optical picture of the packaged supercapacitor prepared in Example 15 immersed in 0.1 M phosphate buffer (PBS) solution at 80°C for 6 weeks.

[0033] Figure 13 Scanning electron microscope (SEM) images (scale bar 5 pm) of the electrodes prepared in Example 3, Comparative Examples 1~3, 8. Wherein a) is the blank molybdenum foil, b), c), d) are the molybdenum oxide electrodes of Comparative Examples 1~3 with oxidation time of 4, 6, 10 minutes respectively, e) is the preferred molybdenum oxide-molybdenum disulfide electrode of Comparative Example 8 (thiourea concentration is 0.8 M), f) is the SEM image of the preferred molybdenum oxide-molybdenum disulfide@polytannic acid electrode of Example 3 (tannic acid concentration is 10 mg / mL, Tris concentration is 10 mM, deposition time is 2 hours).

[0034] Figure 14The scanning electron microscope (SEM) images of the molybdenum oxide-molybdenum disulfide@polytannin electrode sheet prepared in Example 3 after degradation experiment for 1-9 weeks. a)~i) respectively correspond to the microstructure changes of the surface of the electrode material at the 1st week to the 9th week. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative labor fall within the scope of protection of the present application.

[0036] Example 1 Preparation of molybdenum oxide-molybdenum disulfide@polytannin electrode.

[0037] 1) The molybdenum foil was treated with a dilute hydrochloric acid solution for 30 minutes to remove impurities such as oxides on the surface of the molybdenum foil, and then ultrasonically washed with acetone, ethanol and purified water for 10 minutes, and dried at 60°C to obtain a clean molybdenum foil; 2) The clean molybdenum foil was used as a substrate, and molybdenum oxide nanosheets were grown on its surface by anodic oxidation method using an electrochemical workstation. Specifically, the molybdenum foil was used as a working electrode, a platinum (Pt) sheet was used as a counter electrode, and a silver / silver chloride (Ag / AgCl) was used as a reference electrode. In a 1M NaCl electrolyte, a constant voltage of 0-0.8V was applied to the molybdenum foil for oxidation treatment for 6 minutes. During anodic oxidation, the distance between the Pt sheet and the molybdenum foil was kept constant. After oxidation, the oxidized molybdenum foil was carefully rinsed with purified water and dried in a vacuum for 30 minutes to prepare a molybdenum oxide electrode; 3) The prepared molybdenum oxide electrode was transferred to a 50mL high-pressure reaction kettle containing a polytetrafluoroethylene liner, 30mL of 0.8M thiourea was added, and a molybdenum oxide-molybdenum disulfide electrode was prepared by hydrothermal reaction at 180°C for 12 hours; 4) 50mg of tannin acid was taken and added to 10mL of 10mM Tris buffer solution to prepare a tannin acid solution with a concentration of 5mg / mL. The molybdenum oxide-molybdenum disulfide electrode was placed at the bottom of a glass culture dish, and a UV analyzer was used to crosslink at a wavelength of 254nm for 2 hours to prepare a molybdenum oxide-molybdenum disulfide@polytannin electrode.

[0038] Example 2 2 g of polyvinyl alcohol (PVA) gel was dissolved in 10 mL of sodium chloride (NaCl) solution (1 M), first slowly stirred at room temperature for 30 minutes to make the PVA fully swell, then gradually heated to 90 °C and stirred for 3 hours, and after the solution became transparent, the uniform solution was poured into a glass dish, and placed at 4 °C overnight to prepare a PVA / NaCl gel electrolyte.

[0039] The PVA / NaCl gel electrolyte was coated on the surface of the molybdenum oxide-molybdenum disulfide@polytannin electrode prepared in Example 1, the molybdenum oxide-molybdenum disulfide@polytannin electrode was used as the first electrode layer and the second electrode layer, the two coated electrode layers were pasted opposite to each other to assemble a whole in a sandwich-like structure, and a molybdenum oxide-molybdenum disulfide@polytannin supercapacitor was prepared.

[0040] Example 3 The molybdenum oxide-molybdenum disulfide@polytannin electrode was prepared in the same manner as in Example 1, except that the tannin acid concentration was 10 mg / mL.

[0041] Example 4 The degradable supercapacitor was constructed in the same manner as in Example 2, except that the first electrode layer and the second electrode layer used were the molybdenum oxide-molybdenum disulfide@polytannin electrode prepared in Example 3 (tannin acid concentration was 10 mg / mL).

[0042] Example 5 The molybdenum oxide-molybdenum disulfide@polytannin electrode was prepared in the same manner as in Example 1, except that the tannin acid concentration was 20 mg / mL.

[0043] Example 6 The degradable supercapacitor was constructed in the same manner as in Example 2, except that the first electrode layer and the second electrode layer used were the molybdenum oxide-molybdenum disulfide@polytannin electrode prepared in Example 5 (tannin acid concentration was 20 mg / mL).

[0044] Example 7 The molybdenum oxide-molybdenum disulfide@polytannin electrode was prepared in the same manner as in Example 1, except that the Tris concentration was 5 mM.

[0045] Example 8 The degradable supercapacitor was constructed in the same manner as in Example 2, except that the first electrode layer and the second electrode layer used were the molybdenum oxide-molybdenum disulfide@polytannin electrode prepared in Example 7 (Tris concentration was 5 mM).

[0046] Example 9 The molybdenum oxide-molybdenum disulfide@polytannin electrode was prepared in the same manner as in Example 1, except that the Tris concentration was 20 mM.

[0047] Example 10 The degradable supercapacitor was constructed in the same way as Example 2, except that the first electrode layer and the second electrode layer used the molybdenum oxide-molybdenum disulfide@polytannin electrode prepared in Example 9 (the concentration of Tris was 20 mM).

[0048] Example 11 The molybdenum oxide-molybdenum disulfide@polytannin electrode was prepared in the same way as Example 1, except that the ultraviolet analyzer was cross-linked and deposited for 0.5 hours.

[0049] Example 12 The degradable supercapacitor was constructed in the same way as Example 2, except that the first electrode layer and the second electrode layer used the molybdenum oxide-molybdenum disulfide@polytannin electrode prepared in Example 11 (the ultraviolet analyzer was cross-linked and deposited for 0.5 hours).

[0050] Example 13 The molybdenum oxide-molybdenum disulfide@polytannin electrode was prepared in the same way as Example 1, except that the ultraviolet analyzer was cross-linked and deposited for 5 hours.

[0051] Example 14 The degradable supercapacitor was constructed in the same way as Example 2, except that the first electrode layer and the second electrode layer used the molybdenum oxide-molybdenum disulfide@polytannin electrode prepared in Example 11 (the ultraviolet analyzer was cross-linked and deposited for 5 hours).

[0052] Example 15 Packaging of the degradable supercapacitor with self-discharge inhibition function.

[0053] (1) The molybdenum oxide-molybdenum disulfide@polytannin supercapacitor was prepared in the same way as Example 4.

[0054] (2) After the edges of the supercapacitor were coated and packaged with 1 mL of PVA gel, it was placed for 3 hours until it solidified; in addition, 0.1 g of polylactic acid-glycolic acid copolymer (PLGA) was weighed and added to 6 mL of chloroform, which was ultrasonically dissolved and coated on the surface of the supercapacitor, and placed in a fume hood for 12 hours; finally, 12 g of beeswax and 4 g of candelilla wax were weighed and heated and stirred at 80°C until melted, then the supercapacitor was immersed, taken out and naturally dried at room temperature to obtain the molybdenum oxide-molybdenum disulfide@polytannin supercapacitor after wax packaging.

[0055] Comparative Example 1 Preparation of the molybdenum oxide electrode: The molybdenum oxide electrode was prepared according to steps 1) and 2) in Example 1 (the anodic oxidation treatment time was 6 minutes).

[0056] Comparative Example 2 A molybdenum oxide electrode was prepared according to steps 1), 2) in Example 1 except that the anodization treatment time was 4 minutes.

[0057] Comparative Example 3 A molybdenum oxide electrode was prepared according to steps 1), 2) in Example 1 except that the anodization treatment time was 10 minutes.

[0058] Comparative Example 4 Construction of molybdenum oxide supercapacitor. A molybdenum oxide supercapacitor was constructed according to the same method as in Example 2 except that the first electrode layer and the second electrode layer used were the molybdenum oxide electrode prepared in Comparative Example 1 (anodization treatment time of 6 minutes).

[0059] Comparative Example 5 Preparation of molybdenum oxide@polytannic acid electrode. The molybdenum oxide electrode prepared in Comparative Example 1 was placed in a Tris buffer solution (10 mM) containing 10 mg mL -1 of tannic acid and a UV analyzer was used to crosslink for 2 hours to prepare a molybdenum oxide@polytannic acid electrode.

[0060] Comparative Example 6 Construction of molybdenum oxide@polytannic acid supercapacitor. A molybdenum oxide@polytannic acid supercapacitor was constructed according to the same method as in Example 2 except that the first electrode layer and the second electrode layer used were the molybdenum oxide@polytannic acid electrode prepared in Comparative Example 5.

[0061] Comparative Example 7 Preparation of molybdenum oxide-molybdenum disulfide electrode. A molybdenum oxide-molybdenum disulfide electrode was prepared according to the same steps as in 1), 2), 3) in Example 1 except that the thiourea concentration was 0.8 M.

[0062] Comparative Example 8 Preparation of molybdenum oxide-molybdenum disulfide electrode. A molybdenum oxide-molybdenum disulfide electrode was prepared according to the same steps as in 1), 2), 3) in Example 1 except that the thiourea concentration was 0.5 M.

[0063] Comparative Example 9 Preparation of molybdenum oxide-molybdenum disulfide electrode. A molybdenum oxide-molybdenum disulfide electrode was prepared according to the same steps as in 1), 2), 3) in Example 1 except that the thiourea concentration was 1.0 M.

[0064] Comparative Example 10 Construction of molybdenum oxide-molybdenum disulfide supercapacitor. A molybdenum oxide-molybdenum disulfide supercapacitor was constructed according to the same method as in Example 2 except that the first electrode layer and the second electrode layer used were the molybdenum oxide-molybdenum disulfide electrode prepared in Comparative Example 7 (thiourea concentration of 0.8 M).

[0065] Test Example 1 Electrochemical performance tests were performed on the electrodes and supercapacitors prepared in Examples 1-14 and Comparative Examples 1-10 of the present invention, including cyclic voltammetry, constant current charge-discharge test, electrochemical impedance spectroscopy, and self-discharge test.

[0066] 1) Cyclic voltammetry (CV) testing: Using a CHI660E electrochemical workstation, in a three-electrode system, the electrodes prepared in Examples 1, 3, 5, 7, 9, 11, 13 and Comparative Examples 1-3, 5, 7-9 were used as working electrodes, a platinum sheet electrode as the counter electrode, and an Ag / AgCl electrode as the reference electrode. Cyclic voltammetry was performed at 5, 10, 20, 30, 40, 50, and 100 mVs within a voltage range of -0.8 to 0 V. -1 The CV curves of the electrodes were obtained by testing at different scan rates.

[0067] Test results are as follows Figure 1 a) and e) Figure 3 a) and e) Figure 5 a) and e) Figure 7 a) and e) Figure 9 As shown in a) and e).

[0068] In a two-electrode system, the supercapacitors prepared in Examples 2, 4, 6, 8, 10, 12, 14 and Comparative Examples 4, 6, 10 exhibit voltage ranges of 0~1.5V and 5, 10, 20, 30, 40, 50, 60, 80, and 100 mVs. -1 The CV curves of the capacitor were obtained by testing at different scan rates. The test results are as follows: Figure 2 a) and e) Figure 4 a) and e) Figure 6 a) and e) Figure 8 a) and e) Figure 10 As shown in a) and e), the CV curves are nearly rectangular, exhibiting pseudocapacitive characteristics, and the electrochemical reaction is highly reversible. Compared to the molybdenum oxide electrode (Comparative Example 5 and Comparative Example 1) and the molybdenum oxide-molybdenum disulfide@polytannic acid electrode (Example 3 and Comparative Example 7), the area of ​​the CV curve of the molybdenum oxide@polytannic acid electrode after tannic acid deposition is increased, reflecting enhanced charge storage capacity. At the same scan rate, the preferred Example 3 molybdenum oxide-molybdenum disulfide@polytannic acid (tannic acid concentration 10 mg / mL, Tris concentration 10 mM, deposition time 2 hours) electrode and Example 4 capacitor have the largest closed area of ​​the CV curve, indicating that the electrode prepared in Example 3 and the capacitor in Example 4 have stronger charge storage capacity; and at different scan rates (e.g., ... Figure 1 (e) Figure 2 (e)Figure 3 In e), the enclosed area increases with the increase of the scanning speed, and the shape of the curve hardly changes, indicating that the prepared electrode and capacitor have high reversibility of the electrolyte ions in the process of embedding and de-embedding. Figure 4 In e), the enclosed area increases with the increase of the scanning speed, and the shape of the curve hardly changes, indicating that the prepared electrode and capacitor have high reversibility of the electrolyte ions in the process of embedding and de-embedding. Figure 5 In e), the enclosed area increases with the increase of the scanning speed, and the shape of the curve hardly changes, indicating that the prepared electrode and capacitor have high reversibility of the electrolyte ions in the process of embedding and de-embedding. Figure 6 In e), the enclosed area increases with the increase of the scanning speed, and the shape of the curve hardly changes, indicating that the prepared electrode and capacitor have high reversibility of the electrolyte ions in the process of embedding and de-embedding.

[0069] 2) Galvanostatic charge-discharge (GCD) test: In a three-electrode system, using a CHI660E electrochemical workstation, in the voltage range of-0.8~0V, at the current density of 0.5, 1, 2, 4, 6, 8 mA cm -2 The GCD test was performed on the electrodes prepared in Examples 1, 3, 5, 7, 9, 11, 13 and Comparative Examples 1-3, 5, 7-9, and the test results are shown in Table 1. Figure 1 In b) and f), Figure 3 In b) and f), Figure 5 In b) and f), Figure 7 In b) and f), Figure 9 As shown in b) and f), the GCD curve presents a triangular shape, which is basically symmetrical on the left and right, indicating that the surface electrode has high reversibility in the charge-discharge process and presents a pseudo-capacitance characteristic. The specific capacitance of each electrode was calculated according to the GCD curve; At the current density of 0.5 mA cm -2 The specific capacitance values calculated according to the discharge time of Examples 1, 3, 5, 7, 9, 11, 13 and Comparative Examples 1, 2, 3, 5, 7, 8, 9 were 162.38, 227.75, 202.81, 157.12, 183.75, 148.25, 189.68, 52.50, 18.00, 52.00, 66.18, 177.50, 148.56, 146.68 mF cm -2 Figure 1 In c), Figure 3 In c), Figure 5 In c), Figure 7 In c) and g), Figure 9 In c), wherein the preferred Example 3 (tannic acid concentration of 10 mg / mL, Tris concentration of 10 mM, deposition time of 2 hours) has the longest discharge time of 364.4 s and the highest specific capacitance value of 227.75 mF cm -2 .

[0070] The voltage window of the supercapacitor prepared in Examples 2, 4, 6, 8, 10, 12, 14 and Comparative Examples 4, 6, 10 is 0~1.5V, and the charge-discharge condition is evaluated at the current density of 0.5, 1, 2, 4, 6, 8 mA cm -2 The results are shown in Table 2. Figure 2 ​In the middle b) and f), Figure 4 In the middle b) and f), Figure 6 In the middle b) and f), Figure 8 In the middle b) and f), Figure 10 In the middle b) and f), it can be seen that the GCD curve presents a triangular shape, basically symmetrical left and right, and the surface electrode charging and discharging process has high reversibility, showing pseudo-capacitive characteristics. According to the specific capacitance curve of each capacitor calculated from the GCD curve (at 0.5 mA cm -2 The specific capacitance values calculated from the discharge time of examples 2, 4, 6, 8, 10, 12, 14 and comparative examples 4, 6, 10 are 76.53, 90.00, 82.80, 57.00, 81.00, 56.33, 71.76, 25.45, 34.58, 53.13 mF cm -2 Figure 2 In the middle c), Figure 4 In the middle c), Figure 6 In the middle c), Figure 8 In the middle c), Figure 10 In the middle c), wherein the GCD discharge time of the capacitor prepared in example 4 is the longest, and the specific capacitance value is the highest, reaching 90 mF cm -2 .

[0071] The stability of the molybdenum oxide-molybdenum disulfide@polytannin electrode prepared in example 3 and the supercapacitor prepared in example 4 was evaluated, and the results are shown in Figure 11A and Figure 11B As shown in the figures, after 20000 times, the molybdenum oxide-molybdenum disulfide@polytannin electrode still has a capacitance retention rate of 80.68%, and after 5000 times, the molybdenum oxide-molybdenum disulfide@polytannin supercapacitor still has a capacitance retention rate of 81.09%, and the capacitor can light up an LED lamp and drive a timer to run.

[0072] 3) Electrochemical impedance (EIS) test: the electrodes prepared in examples 1, 3, 5, 7, 9, 11, 13 and comparative examples 1-3, 5, 7-9 were tested by EIS under the condition of frequency range of 10 -2 -10 5 Hz and voltage of 5 mV, and the results are shown in Figure 1 In the middle d), Figure 3 In the middle d), Figure 5 In the middle d), Figure 7 In the middle d) and h), Figure 9 In the middle d), the equivalent series resistance (Rs) related to the electrolyte resistance, intrinsic resistance and interface contact resistance can be represented by the value of the real axis intercept, wherein the molybdenum oxide-molybdenum disulfide@polytannin electrode prepared in example 3 has the smallest Rs of 3.72 Ω, indicating that it has the best conductivity.​

[0073] 4) Self-discharge test: The open-circuit voltage measurement method (OCP) was used to evaluate the self-discharge resistance of the device. The supercapacitor was charged to 1.5V, and the voltage decay of the device over 12 hours was observed. The self-discharge test results of Examples 2, 4, 6, 8, 10, 12, 14 and Comparative Examples 4, 6, 10 are as follows: Figure 2 d) Figure 4 d) Figure 6 d) Figure 8 d) Figure 10 As shown in d), the molybdenum oxide-molybdenum disulfide@polytannic acid supercapacitor prepared in the preferred embodiment 4 has a self-discharge rate of 76.17 mV / h. -1 All of these values ​​are lower than the self-discharge rate of 103.91 mV / h of the molybdenum oxide-molybdenum disulfide@polytannic acid capacitors prepared in Examples 2, 6, 8, 10, 12, and 14. -1 81.58mV h -1 90.67mV h -1 85.25mV h -1 106.25mV h -1 99.83mV h -1 Furthermore, it is significantly lower than the self-discharge rate of 112.33 mV / h of the molybdenum oxide-molybdenum disulfide capacitor without tannic acid deposition (Comparative Example 8). -1 Additionally, in Comparative Example 6, a molybdenum oxide@polytannic acid capacitor with deposited tannic acid (63.82 mV h) -1 It was also lower than that of the molybdenum oxide capacitor without tannic acid deposition in Comparative Example 4 (91.38 mV h). -1 The self-discharge rate of the capacitor indicates that the polytannic acid coating can hinder the parasitic Faraday reaction of impurity ions on the electrode surface and prevent charge transfer, thereby reducing the self-discharge rate of the capacitor and demonstrating good anti-self-discharge performance.

[0074] Test Example 2 Electrode and capacitor degradation performance testing: Electrode degradation experiment: The molybdenum oxide-molybdenum disulfide@polytannic acid electrode sheet prepared in Example 3 was immersed in a 0.1M phosphate buffer (PBS) solution simulating a body fluid environment (PBS solution preparation: 80g NaCl, 2g KCl, 15.4g Na2HPO4·12H2O and 0.20g KH2PO4 were dissolved in 1L purified water under stirring at room temperature), and kept in a 37℃ water bath. The degradation process was recorded by taking optical images and weighing the changes in mass. Figure 12AOptical pictures of the degradation process of the molybdenum oxide-molybdenum disulfide@polytannin electrode sheet in 15 weeks, the material gradually cracks over time and finally degrades substantially at 15 weeks; Figure 12B The mass change diagram of the molybdenum oxide-molybdenum disulfide@polytannin electrode sheet in the degradation process in 15 weeks is consistent with the result observed by macroscopic observation, the mass of the electrode gradually decreases over time, and tends to 0 at 15 weeks, indicating that the electrode material can be degraded and metabolized in the simulated human body fluid environment.

[0075] Capacitor degradation experiment: the encapsulated supercapacitor of Example 15 was immersed in a PBS solution at 80°C, and the degradation process of the supercapacitor with a wax layer was observed. Figure 12C Optical pictures of the assembled supercapacitor immersed in a 0.1M phosphate buffer (PBS) solution at 80°C for 6 weeks. As can be seen from the figure, the PLGA layer and the wax layer outside the device gradually degrade in 12 hours, and the encapsulated capacitor degrades completely in 6 weeks.

[0076] Test Example 3 Electrode material apparent morphology characterization: The electrode material was characterized by scanning electron microscopy (SEM), as shown in Figure 13 , wherein Figure 13 In a), the blank molybdenum foil material has a smooth and flat surface. Figure 13 In b), c), and d), they are Comparative Examples 1-3, i.e., the molybdenum oxide materials obtained by oxidation for 4, 6, and 10 minutes, respectively. Compared with the smooth morphology of the molybdenum foil surface, the molybdenum foil surface after oxidation treatment has a crack layer, indicating that a molybdenum oxide layer is formed on the surface of the molybdenum foil. Figure 13 In e), it is the molybdenum oxide-molybdenum disulfide material of Comparative Example 7. Compared with the molybdenum oxide electrode material of Comparative Example 1, its surface presents a nanosheet structure, and the sulfurization reaction on the surface successfully grows molybdenum disulfide nanosheets on the surface of the molybdenum oxide. Figure 13 In f), it is the molybdenum oxide-molybdenum disulfide@polytannin material of Example 3. Compared with the above molybdenum oxide-molybdenum disulfide, the tannin coating structure can be obviously observed on the surface.

[0077] The morphology of the molybdenum oxide-molybdenum disulfide@polytannin electrode prepared in Example 3 was characterized during the degradation process, and the scanning electron microscope (SEM) image is shown in Figure 14 , wherein Figure 14 In a)~i), they are the SEM images of the electrode after the degradation experiment from the 1st week to the 9th week, and it can be seen that the material gradually degrades and falls off layer by layer over time, which is consistent with the result observed by macroscopic optical picture observation.

[0078] Although the present application has been described in detail with reference to the foregoing embodiments, it should be understood that modifications can be made to the foregoing embodiments, or additional implementations can be implemented, without departing from the spirit and scope of the inventive subject matter. Accordingly, the present application is not limited to the implementations described herein, but is intended to be defined by the claims set forth below, and equivalents thereof.

Claims

1. A method for preparing a molybdenum oxide-molybdenum disulfide@polytannin electrode material, characterized in that, The method comprises the following steps: The molybdenum foil is cleaned and then the molybdenum oxide nanosheet is grown on the surface of the molybdenum foil by an anodic oxidation method; Thiourea is added to the reaction container containing the molybdenum oxide nanosheet to perform a hydrothermal reaction to prepare a molybdenum oxide-molybdenum disulfide electrode material; The molybdenum oxide-molybdenum disulfide electrode material is placed in a buffer solution of tannic acid, and a polytannic acid coating is deposited on the surface of the electrode material by ultraviolet irradiation to obtain a molybdenum oxide-molybdenum disulfide@polytannic acid electrode material.

2. The method for preparing a molybdenum oxide-molybdenum disulfide@polytannin electrode material according to claim 1, characterized in that, The method further comprises sequentially performing ultrasonic cleaning on the molybdenum foil by using hydrochloric acid, acetone, anhydrous ethanol and purified water; The anodic oxidation method adopts a three-electrode system, the voltage window is 0~0.8V, the scanning rate is 0.08~0.1Vs -1 , and the oxidation time is 4~10 minutes.

3. The method for preparing the molybdenum oxide-molybdenum disulfide@polytannin electrode material according to claim 1, characterized in that, The specific conditions of the hydrothermal reaction are as follows: the hydrothermal reaction is performed at 160-200 ℃ for 10-14 hours; The concentration of the thiourea solution is 0.5-1.0 M.

4. The method for preparing the molybdenum oxide-molybdenum disulfide@polytannic acid electrode material according to claim 1, characterized in that, The buffer solution is a tris-hydroxymethyl aminomethane hydrochloride buffer solution, and the concentration is 5-20 mM; The concentration of the tannic acid in the buffer solution is 5-20 mg / mL; The wavelength of the ultraviolet light is 254-365 nm, and the irradiation time is 0.5-5 hours.

5. A molybdenum oxide-molybdenum disulfide@polytannin electrode material, characterized in that, The molybdenum oxide-molybdenum disulfide@polytannic acid electrode material is prepared by using the preparation method of any one of claims 1-4.

6. A method of inhibiting self-discharge behavior of a supercapacitor, characterized by, The molybdenum oxide-molybdenum disulfide@polytannic acid electrode material is used as an electrode of a supercapacitor.

7. A molybdenum oxide-molybdenum disulfide@polytannin supercapacitor, characterized in that, The supercapacitor comprises a first electrode layer, a second electrode layer and an electrolyte layer arranged between and in contact with the first electrode layer and the second electrode layer; The first electrode layer and / or the second electrode layer is the molybdenum oxide-molybdenum disulfide@polytannic acid electrode material of claim 5; The electrolyte layer is a polyvinyl alcohol / sodium chloride gel electrolyte.

8. A method for preparing a molybdenum oxide-molybdenum disulfide@polytannin supercapacitor, characterized in that, The method comprises the following steps: Polyvinyl alcohol is dissolved in a sodium chloride solution at a concentration of 0.1-0.3 g / mL, and after stirring, the solution is left to stand until it becomes transparent to obtain a polyvinyl alcohol / sodium chloride gel electrolyte; The first electrode layer and the second electrode layer of claim 7 are coated with the polyvinyl alcohol / sodium chloride gel electrolyte, and the coated first electrode layer and the second electrode layer are pasted to form a supercapacitor; Polylactic acid-glycolic acid copolymer and chloroform are mixed at a ratio of 0.01-0.03:1 g / mL, and after ultrasonic dissolution, the mixture is coated on the surface of the supercapacitor and left to stand in a ventilated condition for 10-14 hours; The ventilated supercapacitor is immersed in a liquid obtained by melting a mixture of beeswax and candelilla wax, and after being taken out, the supercapacitor is naturally dried at room temperature to obtain an encapsulated molybdenum oxide-molybdenum disulfide@polytannic acid supercapacitor.

9. The method for preparing the molybdenum oxide-molybdenum disulfide@polytannic acid supercapacitor according to claim 8, characterized in that, During the preparation of the polyvinyl alcohol / sodium chloride gel electrolyte: The concentration of the sodium chloride solution is 0.5-2 M; The dissolution conditions of the polyvinyl alcohol in the sodium chloride solution are as follows: stirring at room temperature for 20-40 minutes, and then stirring at 80-100 ℃ for 2-4 hours after heating; The standing condition is standing at 2-6 ℃ for 12-24 hours.

10. The method for preparing the molybdenum oxide-molybdenum disulfide@polytannic acid supercapacitor according to claim 8, characterized in that, The ratio of the amount of the polylactic acid-glycolic acid copolymer to chloroform is 0.01-0.03:1 g / mL; The mass ratio of the beeswax to the candelilla wax is 2-4:1; The heating temperature of the beeswax and the candelilla wax is 70-90 ℃.

Citation Information

Patent Citations

  • Preparation method of symmetrical super capacitor with high power density

    CN108010731A

  • Tannic acid modified molybdenum disulfide oxide, preparation method of tannic acid modified molybdenum disulfide oxide, tannic acid modified molybdenum disulfide oxide composite film and preparation method of tannic acid modified molybdenum disulfide oxide composite film

    CN118754201A

  • Composition of galvanized steel sheet for surface-treatment, method of surface-treating galvanized steel sheet and galvanized steel sheet

    KR1020140083833A